Antinociceptive Effects of Sinomenine Combined With Ligustrazine or Paracetamol in Animal Models of Incisional and Inflammatory Pain - Gao, Tianle; Li, Tao; Jiang, Wei; Fan, Weiming; Xu, Xiao-Jun; Zhao, Xiaoliang; Yin, Zhenming; Guo, Huihui; Wang, Lulu; Gao, Jun; Han, Yanxing; Jiang, Jian-Dong; et al. (Frontiers in Physiology, 2021)
The management of postoperative and inflammatory pain has been a pressing challenge in clinical settings. Sinomenine (SN) is a morphinan derived alkaloid with remarkable analgesic properties in various kinds of pain models. The aim of the current study is to investigate if SN can enhance the effect of ligustrazine hydrochloride (LGZ) or paracetamol (PCM) in animal models of postoperative and inflammatory pain. And to determine if the combined therapeutic efficacies can be explained by pharmacokinetics changes. Pharmacological studies were performed using a rat model of incisional pain, and a mouse model of carrageenan induced inflammatory pain. Pharmacokinetic studies were performed using a HPLC-QQQ-MS method to quantify SN, LGZ and PCM levels in blood and extracellular fluids in brain. We found that SN plus LGZ or SN plus PCM produced marked synergistic analgesic effects. However, such synergy was subjected to pain modalities, and differed among pain models. Pharmacological discoveries could be partially linked to pharmacokinetic alterations in SN combinations. Though further evaluation is needed, our findings advocate the potential benefits of SN plus LGZ for postoperative pain management, and SN plus PCM for controlling inflammatory pain.